2007
DOI: 10.1002/jcb.21482
|View full text |Cite
|
Sign up to set email alerts
|

Low substratum rigidity of collagen gel promotes ERK phosphorylation via lipid raft to augment cell migration

Abstract: Previous study demonstrated that low substratum rigidity down-regulates focal adhesion proteins. In this study we found that cells cultured on collagen gel exhibited higher migration capacity than those cultured on collagen gel-coated dishes. Low rigidity of collagen gel induced delayed but persistent phosphorylation of ERK1/2. Inhibition of collagen gel-induced ERK1/2 phosphorylation by MEK inhibitors and ERK2 kinase mutant induced a rounding up of the cells and prevented collagen gel-induced cell migration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This connection initiates signaling to the cell by clustering a complex of proteins collectively termed focal adhesions 5 6 7 and recently multimolecular integrin adhesion complex 8 9 . Focal adhesion proteins such as vinculin and focal adhesion kinase (FAK) are critical for the process of cell invasion in extracellular matrices 10 11 12 13 14 .…”
mentioning
confidence: 99%
“…This connection initiates signaling to the cell by clustering a complex of proteins collectively termed focal adhesions 5 6 7 and recently multimolecular integrin adhesion complex 8 9 . Focal adhesion proteins such as vinculin and focal adhesion kinase (FAK) are critical for the process of cell invasion in extracellular matrices 10 11 12 13 14 .…”
mentioning
confidence: 99%
“…Integrins are known to be involved in cell adhesion, transmigration and invasion processes and in coupling of the actomyosin cell cytoskeleton to the microenvironment. The activation of integrin receptors could be through conformational changes after ligand binding and possibly through biomechanical stimulation [17,50]. The activation of integrins may be regulated through either increased affinity to ligands by enhancing the number of activated integrins and total integrins on the cell's surface or integrin translocation into lipid rafts, whereas this has only been reported for β1 integrin subunits [50].…”
Section: Discussionmentioning
confidence: 99%
“…This coupling is an initiation signal for focal adhesion proteins to cluster underneath the cell membrane to focal contacts and focal adhesions [13]. Thus, focal adhesion proteins such as vinculin and focal adhesion kinase are critical for the process of cellular motility into ECM [14][15][16][17]. In focal adhesions, cell surface transmembrane receptors of the integrin family promote the extracellular interaction with ECM ligands and couple the microenvironment with the cytoskeletal actin-microfilament system [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, immunoelectron microscopy studies have shown that ERK1/2 is concentrated in plasma membrane caveolae (17). In addition, research based on epithelial cells has revealed translocation of phosphorylated ERK1/2 to caveolin lipid rafts due to reduction in substrate rigidity (44). As cells in 3D culture are surrounded by naturally soft ECM, all these results suggest that accumulation of activated ERK1/2 into lipid rafts of different cell types may be a common phenomenon, taking place when the substrate stiffness is low.…”
Section: Discussionmentioning
confidence: 99%